Neo-Protectionism and the European Lobbies - Marianna Belloc (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper empirically explores the connection between two recent phenomena in the European scenario: the dramatic upsurge of non-tariff trade measures and the remarkable rise in the role of European business lobbies. While these two facts have been widely recognized by the international trade and the political economy literature, empirical investigation into the connection between the two has so far been impeded by the lack of data. To identify European special interest groups and their influence on policy decisions, we construct an original dataset by collecting information on the participation of national and international organizations in the European Commission consultations on trade issues and by merging it with newly released information on non-tariff measures aggregated at the tariff-line level. Drawing upon the panel structure of the dataset, we find that European lobbies exert an important influence on the policy-makers, even after controlling for product fixed effects and a number of product and industrial variables. Between two possible interpretations of this finding, either that participation in meetings captures political pressure (possibly including the supply of biased information) on policy-decisions or that it involves, rather, transmission of true information, our empirical results tend to favor the former. Nonetheless, we are inclined to rule out the possibility that registration in consultations is in itself just signaling for active involvement in lobbying action, since we find evidence that actual meeting attendance has a larger impact on policy decision than registration only.
Keywords: F14; F15; D72; 330; trade policy; neo-protectionism; European Union; lobbying; political economy